Corrigendum: The influence of artificial intelligence on the manufacturing industry in South Africa - Manqoba L. Nzama; Ayogeboh Epizitone; Smangele P. Moyane; Ntando Nkomo; Peggy P. Mthalane (South African Journal of Economic and Management Sciences, 2024)
No abstract available.